Oltre la retorica della bella città innevata - Federico Di Cosmo; Björn Ekelund; Agatino Rizzo (Quodlibet, 2020)
In winter cities it is normal that piled-up snow, perhaps moved by the wind or the snowplows, subtracts a large part of the public space, the surfaces compacted by the trampling become dangerously slippery, the melting water, the ice and the slush behave as physical and mental barriers to soft mobility, that seasonal deposits capture large quantities of pollutants and congest the water disposal system. In the virtuous panorama of the urban policies of the Nordic countries, Gällivare (Sweden) represents an innovative case, which places new tools on the table of best practices to improve the winter livability of the urban environment. With the adoption of the Blue, Green and White masterplan (2016), in fact, the small Arctic town transforms the snow from a climate constraint to an abundant large-scale resource, through which promote a vibrant environment, full of recreational possibilities. A new model of circular management of ecological infrastructures summarizes a series of experimental principles about the transformation of the snowpack into a system of temporary large-scale architectures, attractive and multifunctional, aesthetically and technically coordinated with the blue and green spaces.